PENERAPAN MODEL PEMBELAJARANKOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DALAM MENINGKATKAN HASIL BELAJAR MATA PELAJARAN MENGAIRI PADA SISWA KELAS X ATPH1 SMKN 3 TAKALAR - Rudi Harza; Bakhrani Andi Rauf; Suardy Suardy (Universitas Negeri Makassar, 2015)
This is a class action research. The purpose of this research is to evaluate the result of the student’s achievement in irrigation subject using cooperative learning model with Numbered Heads Together (NHT) technique on class X students of SMKN 3 Takalar ATPH1. The subjects of this research on class X students of SMKN 3 Takalar in Horticulture and Agribusiness Food Crops major with totaling 32 students consisting of 25 men and 7 women. The results of this research shows that the application of cooperative learning model with Numbered Heads Together (NHT) technique in irrigation subject on class X of SMKN 3 Takalar ATPH1 can improve the student’s achievement in irrigation. It is proved by the result of the student’s score in the first and the second cycle through the implementation of cooperative learning model with Numbered Heads Together (NHT) technique. The Student’s score average in the first cycle is 74.90%, while the classical standard reaches 65.625%. The implementation of the second cycle is increased with an average score 86.375%, while for classical standard reaches 93.75%. In another word, 30 from 32 students are in the completed category